O pagode de viola de Tião Carreiro: configurações estilísticas, importância e influências no universo da música violeirística brasileira - Malaquias, Denis Rilk (2013)
This research aims to study the genre pagode of viola of musician Tião Carreiro, approached from of the processes of cultural interaction which is resulting and their stylistic peculiarities, aiming to investigate the importance and influences exerted on the scenario of violeirística Brazilian music. For both analyzes were carried out of works and violeirísticas performances of Tião Carreiro and musicians who have excelled in three different cuts time after him, seeking to evidence the dialogue of these musicians with their work and performance, assess the characteristics of contextual style (the genre), living with characteristics of individual style (resulting from updates from genre effected for them) according reflections of Bakhtin (2003). In the course of the research it was possible to show that musicians of various musical facets, especially related to country music and music violeirística, in a general way, revere the work of Tião Carreiro, and that pagode of viola has influenced generations of viola players.